Implementasi Program Pendaftaran Tanah Sistematis Lengkap (PTSL) Dalam Mewujudkan Tertib Hukum Administrasi Pertanahan di desa Kabuaran, kecamatan Kunir, kabupaten Lumajang - Sulastini, Sulastini (Jurnal Ilmiah Wahana Pendidikan, 2024)
The implementation of this research aims to find out the implementation and analyze the factors that hinder the complete systematic land registration (PTSL) program in realizing the legal order of land administration in Kabuaran Village, Kunir sub-district, Lumajang district. This research uses an empirical juridical approach, the data collection techniques used are interviews and documentation. The results of interview research and legal analysis that the implementation of the Complete Systematic Land Registration Program (PTSL) has been running to realize the legal order of land administration in Kabuaran village, Kunir sub-district, Lumajang district.